2015
DOI: 10.1111/jpn.12319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different levels of raw and heated grass pea seed (Lathyrus sativus) on nutrient digestibility, intestinal villus morphology and growth performance of broiler chicks

Abstract: This study aimed to investigate chemical composition and effect of different levels (0%, 10% and 20%) of raw grass pea (RGP) and heat-treated (120 °C for 30 min) grass pea seed (HGP) on nutrient digestibility, dressing percentage, relative internal organ weights, intestinal villous morphology and broiler chicks' performance. A total number of 200 day-old male chicks were raised under similar condition for 10 days. On day 11, chicks were randomly assigned to five dietary treatments and four replicates of 10 bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(33 reference statements)
0
2
0
1
Order By: Relevance
“…The effect of different levels of raw grass pea caused a remarkable decrease in gross energy and lipid apparent digestibility (Riasi et al, 2015). Spielmann et al (2008) observed that pea protein has a low methionine content and a high arginine content.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of different levels of raw grass pea caused a remarkable decrease in gross energy and lipid apparent digestibility (Riasi et al, 2015). Spielmann et al (2008) observed that pea protein has a low methionine content and a high arginine content.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the study, the blood Cl levels of lambs were close to the lower limit of normal blood Cl levels, but after the experiment, the blood Cl levels of the lambs increased in all groups independent of the CV consumption. In the literature, the chlorine content of CV has been reported as 0.50 g kg -1 (Riasi et al 2014;Riasi et al 2015), while the chlorine content of SH has been reported as 0.32 g kg -1 (Xionga et al 2008). Since the chlorine contents of CV and SH were similar, it was thought that the rumen development was caused by the increase in blood Cl levels of lambs.…”
Section: Resultsmentioning
confidence: 98%
“…Сообщалось об изменении морфологии кишечника (укорочение ворсинок, уменьшение площади их поверхности и глубины крипт) у бройлеров, в рацион которых входил горох, по сравнению с птицей, получавшей сою (32). При добавлении к рациону 20 % сырых или термически обработанных семян чины посевной (Lathyrus sativus) отмечали изменения размера поджелудочной железы и глубины крипт кишечника (33). Данных о влиянии гороха в рационе на гистоструктуру печени птицы в доступной литературе мы не обнаружили.…”
Section: биоконтроль инкубации яиц от 658-недельных кур-несушек (Gallusunclassified